Participation in Recreational Activities and Stress Management Relationship Among High School Teachers in Lopez Jaena (American Journal of Arts and Human Science, 2022)
The study aimed to determine the relationship between participation in recreational activities and stress management among high school teachers in Lopez Jaena during SY 2018–2019. The study used an evaluative-inferential research design that used quantitative and qualitative descriptive-correlational approaches to interpret the data. There were 119 respondents, with 34 males and 85 females. The instruments were adopted from those made by Prof. Henry C. Daut’s SPEAR 174 class in 1994 for participation in recreational activities and by Della Franklin in 2008 for managing stress. The study found that most of the respondents were young adults or middle-aged females; the majority were Cebuano; married; most were regular or permanent employees, with salary income ranging from ₱10, 001.00 to ₱20, 000.00. Almost all the respondents participated in one recreational activity. The relationship between the variables showed that daily schedule is related to monthly income; money involvement in recreation is related to age; cost of money is related to sex; venue/place is related to ethnicity; off-campus is related to the tenure of work and monthly income; recreation activities are related to age, and involvement in recreation is related to age. It was also found that the correlation between moderating variables and stress management revealed a highly significant relationship with ethnicity. It was concluded that the correlation between recreational activities and stress management revealed that the cost of participating in recreational activities is highly correlated with stress management. Results from this study suggest that policymakers create ideas and plan programs to engage teachers in recreational activities to lessen work-related stress. The school administration should also provide a recreational activity center that will cater to the recreational activities needed for the development of recreation among schoolteachers. Future researchers should conduct similar studies using a broader scope.